Exact values of widths for the classes of functions defined by the averaged smoothness characteristics and majorants in the space L_2 - Vakarchuk, S.; Zabutna, V.; Vakarchuk, M. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5 Exact values of various widths are determined in the space L_2 for the classes 2π-periodic functions constructed with the use of the averaged smoothness characteristics and majorants under certain restrictions imposed on the majorants. Several specific examples are considered with an aim to clarify the obtained result. The presented new results can be regarded as a logical extension of the results of our previous investigations.